Fluid-assisted zircon and monazite growth within a shear zone: A case study from Finnmark, Arctic Norway - Kirkland, Chris; Whitehouse, M.; Slagstad, T. (Springer, 2009)
The U-Pb ages, REE content, and oxygen isotopic composition of zircon rims developed within a major shear zone in the Kalak Nappe Complex (KNC), Arctic Norway have been determined along with the age of monazite crystals. Different generations of granitic veins have been distinguished based on both field criteria and monazite ages of 446 ± 3 and 424 ± 3 Ma. Within each of these veins, inherited zircon cores are mantled by homogeneous low CL-response zircon rims which yield a range of concordant U-Pb dates of ca. 470-360 Ma. Significant numbers of zircon rims coincide with the timing of monazite crystallization. The zircon rims have moderate light REE enrichment compared to cores, distinctive (Sm/La)n values of less than 12, and La between 0.3 and 10 ppm. This indicates free elemental exchange between newly formed zircon rims and the surrounding matrix. The rims have calculated accumulated alpha-radiation dosages corresponding with a crystalline structure and d18O values of 1‰. This implies rim crystallization directly from a zirconium-saturated hydrothermal fluid which was modified by some silicate melt. Growth of the zircon rims was prolonged and locally variable due to preferential fluid flow. A third type of zircon can be recognized, forming both rims and cores, with high alpha-radiation doses, and significant enrichment in La, Pr, and Eu. These are interpreted as low-temperature hydrothermally altered metamict zircons. The high volatile input and partial melting in the shear zone favoured prolonged zircon rim growth due to its ability to easily nucleate on inherited seeds. On the other hand, monazite, susceptible to dissolution and re-growth, crystallized in brief episodes, as has been predicted from theoretical phase diagrams. From a regional perspective, these results elucidate cryptic Ar-Ar cooling ages, providing the first record of a Late Ordovician heating and cooling phase within the KNC prior to the climactic Scandian collision. © Springer-Verlag 2009.